Nilai Budaya dalam Cerita Rakyat Penamaan Desa Pacalan Kecamatan Plaosan Kabupaten Magetan - Santikasari, Eka Bibit; Syaiful Rizal, Maulfi (Universitas Muhammadiyah Surabaya, 2025)
This research examines the cultural value of folklore related to the naming of Pacalan Village, Plaosan District, Magetan Regency, which is related to the story of Ki Ageng Kembang Sore. As an influential ulama figure, Ki Ageng Kembang Sore is known for his contribution to the spread of Islam in this region, as well as his role in creating the cultural and social identity of the local community. Using a descriptive qualitative approach and ethnographic methods, this research explores the moral values, such as wisdom, courage and justice, contained in the story. Data collection is very dependent on the researcher's ability to understand the situation that is the focus of his research, obtained through in-depth interviews with community leaders and participatory observation, and supported by historical documentation. Analysis is carried out including reduction, presentation and drawing conclusions. This research found that the Ki Ageng Kembang Sore folklore plays an important role for the people of Pacalan Village in understanding cultural values ​​such as religious values ​​and respect for ancestors, religious values ​​and traditional values ​​in celebrating their local culture and history, which supports the preservation of oral traditions in facing the challenges of modernization. It is hoped that this research can contribute to efforts to preserve cultural wealth